Mechanical Conflicts in Twisting Growth Revealed by Cell-Cell Adhesion Defects - Verger, Stéphane; Liu, Mengying; Hamant, Olivier (Frontiers in Plant Science, 2019)
Many plants grow organs and tissues with twisted shapes. Arabidopsis mutants with impaired microtubule dynamics exhibit such a phenotype constitutively. Although the activity of the corresponding microtubule regulators is better understood at the molecular level, how large-scale twisting can emerge in the mutants remains largely unknown. Classically, oblique cortical microtubules would constrain the deposition of cellulose microfibrils in cells, and such conflicts at the cell level would be relaxed at the tissue scale by supracellular torsion. This model implicitly assumes that cell-cell adhesion is a key step to transpose local mechanical conflicts into a macroscopic twisting phenotype. Here we tested this prediction using the quasimodo1 mutant, which displays cell-cell adhesion defects. Using the spriral2/tortifolia1 mutant with hypocotyl helical growth, we found that qua1-induced cell-cell adhesion defects restore straight growth in qua1-1 spr2-2. Detached cells in qua1-1 spr2-2 displayed helical growth, confirming that straight growth results from the lack of mechanical coupling between cells rather than a restoration of SPR2 activity in the qua1 mutant. Because adhesion defects in qua1 depend on tension in the outer wall, we also showed that hypocotyl twisting in qua1-1 spr2-2 could be restored when decreasing the matrix potential of the growth medium, i.e. by reducing the magnitude of the pulling force between adjacent cells, in the double mutant. Interestingly, the induction of straight growth in qua1-1 spr2-2 could be achieved beyond hypocotyls, as leaves also displayed a flat phenotype in the double mutant. Altogether, these results provide formal experimental support for a scenario in which twisted growth in spr2 mutant would result from the relaxation of local mechanical conflicts between adjacent cells via global organ torsion.